Предмет: Алгебра,
автор: ChebupelkaТян
__________________
Упростить выражение
__________________
Приложения:
Ответы
Автор ответа:
0
((√a+1)/(√a-1)-4√a/(a-1))/((√a-1)/(a+√a))
Упростим выражение в скобках:
((√a+1)*(√a+1)-4√a))/(a-1)=((√a+1)²-4√a)/(a-1)=(a+2√a+1-4√a)/(a-1)=
=(a-2√a+1)/(a-1)=(√a-1)/((√a-1)(√a+1))=1/(√a+1) ⇒
(1/(√a+1))/((√a-1)/(√a(√a+1))=√a/(√a-1).
Упростим выражение в скобках:
((√a+1)*(√a+1)-4√a))/(a-1)=((√a+1)²-4√a)/(a-1)=(a+2√a+1-4√a)/(a-1)=
=(a-2√a+1)/(a-1)=(√a-1)/((√a-1)(√a+1))=1/(√a+1) ⇒
(1/(√a+1))/((√a-1)/(√a(√a+1))=√a/(√a-1).
Похожие вопросы
Предмет: Другие предметы,
автор: sed46478
Предмет: Русский язык,
автор: tugekama
Предмет: Физика,
автор: sanicdehegog
Предмет: Математика,
автор: Аноним